Strategic planning and its influence on competitiveness in the Bolognesi Shopping Center, Tacna Region - Apaza Paucara, Juan Carlos (2022)
This article is a previously prepared work, whose stated objective was to determine that strategic planning influences competitiveness in the Bolognesi Shopping Center, Tacna Region, 2019. Quantitative approach, type of basic research, non-experimental cross-sectional design and explanatory level. . The collection of data has been applying two instruments for measuring the constructs: strategic planning and competitiveness, adapted and validated. For this purpose, 110 microentrepreneurs were selected, with a reliability of Cronbach's alpha of 0.943 and 0.881, respectively. At a general level, the conclusions made it possible to determine the evidence in favor of a relationship and the level of influence of strategic planning on competitiveness, with a Spearman's Rho association value of 0.693, moderate positive correlation, with a p value = 0.000 < 0.05, and at a confidence level of 95 %, likewise, at an explanatory level, in the ordinal logistics test, the strategic planning predictive construct contributes with a probability of 6.1 times in the competitiveness of the shopping center. Similarly, the value of Nagelkerke's R square indicates that the proposed model explains 40.0 % of the variance of the dependent variable. Consequently, strategic planning significantly influences the competitiveness of microentrepreneurs, to the extent that it is a priority tool in daily practice in the management and operations of the shopping center: strategic conceptions, organizational values, internal and external factors and strategies; in being competitive.